Architecture as a relation of doing and being (ARTEKS : Jurnal Teknik Arsitektur, 2020)
ARTEKS : Jurnal Teknik Arsitektur, volume 5, issue 3, December 2020 presents the fifteen on the conception of research results, which defined architecture as an inseparable coin related to "doing" and "being".The implication of the fifteen articles in the ARTEKS : Jurnal Teknik Arsitektur, volume 5 issue 3, December 2020 is that architecture is a relation and not a subject, object, doing, or being.
Keywords: Being contemplation; Relationship being and doing; The language of architecture